Body size prediction in scorpions: a phylogenetic comparative examination of linear measurements of individual body parts - Foerster,Stênio Í. A. (PeerJ, 2025)
Body size has always been the focus of several ecological studies due to its undeniable influence on other life-history traits. The conventional representation of body size in arthropods typically relies on linear measures, such as total body length, or the length of specific body parts that can be used to represent body size. While these measures offer simplicity over more complicated alternatives (e.g., dry mass), technical problems persist for arthropods with complex body structures, as is the case for scorpions. In these animals, accurate measurements often require extensive handling, including the stretching of body parts. In light of the difficulties associated with directly measuring total length and carapace length in scorpions (two prevalent proxies for body size in the group), this study evaluates the ability of seven simple linear measurements in predicting length measures of boy size in scorpions under a phylogenetic framework. Predictive equations derived from phylogenetic mixed linear models fitted under Bayesian framework were implemented in custom R functions that can be applied for size prediction in a wide range of scorpions. Overall, accurate predictions of total length and carapace length could be achieved using any of the studied traits as single predictors. However, the most accurate predictions for total length were obtained using the length of metasomal segment V, while the best predictions for carapace length were achieved using telson length. The addition of a secondary predictor had low impact on the quality of the size predictions, indicating that increasing model complexity by incorporating additional predictors is not necessary to achieve accurate size estimates. Technical advantages and limitations associated with each linear measurement are discussed. In conclusion, this study broadens the repertoire of methods available for accurately estimating body size in scorpions, particularly in instances where body size information can only be obtained indirectly through allometric relationships.
Keywords: Body size; Scorpions; Allometry; Arachnida; Phylogeny; Size prediction; Arthropoda